2011
DOI: 10.1103/physrevb.84.064116
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry analysis for the Ruddlesden-Popper systems Ca3Mn2O7and Ca

Abstract: We perform a symmetry analysis of the zero-temperature instabilities of the tetragonal phase of Ca 3 Mn 2 O 7 and Ca 3 Ti 2 O 7 which is stable at high temperature.We introduce order parameters to characterize each of the possible lattice distortions to construct a Landau free energy which elucidates the proposed group-subgroup relations for structural transitions in these systems. We include the coupling between the unstable distortion modes and the macroscopic strain tensor. We also analyze the symmetry of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
48
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 44 publications
2
48
2
Order By: Relevance
“…The same combination of irreps (X − 3 ⊕ X + 2 ) that induces the polar distortion in A2 1 am also can induce this antipolar distortion, when the irreps are taken along different directions in OP space. The key to describing these polar and antipolar structures on an equal footing is to use the full two-dimensional OPs 24,25 to describe the structural distortions in Ca 3 Ti 2 O 7 . This means that both an amplitude Q and a phase θ characterize each distortion.…”
Section: Introductionmentioning
confidence: 99%
“…The same combination of irreps (X − 3 ⊕ X + 2 ) that induces the polar distortion in A2 1 am also can induce this antipolar distortion, when the irreps are taken along different directions in OP space. The key to describing these polar and antipolar structures on an equal footing is to use the full two-dimensional OPs 24,25 to describe the structural distortions in Ca 3 Ti 2 O 7 . This means that both an amplitude Q and a phase θ characterize each distortion.…”
Section: Introductionmentioning
confidence: 99%
“…Within this context, an oxide class referred to as hybrid-improper ferroelectrics (HIF) 11 has garnered interest owing to strong anharmonic interactions among polar and nonpolar BO 6 rotational modes 12,13 . Such multimode interactions are responsible for the appearance of an electric polarization 14 with the layered A 3 B 2 O 7 Ruddlesden-Popper (RP) structure serving as the scaffolding 11,15,16 …”
mentioning
confidence: 99%
“…Within this context, an oxide class referred to as hybrid-improper ferroelectrics (HIF) 11 has garnered interest owing to strong anharmonic interactions among polar and nonpolar BO 6 rotational modes 12,13 . Such multimode interactions are responsible for the appearance of an electric polarization 14 with the layered A 3 B 2 O 7 Ruddlesden-Popper (RP) structure serving as the scaffolding 11,15,16 to stabilize the polar ground state structure (that is, Cmc2 1 symmetry) and induce an electric polarization P. The first theoretically proposed HIF RP oxides include Ca 3 B 2 O 7 (B = Ti or Mn) 11 , which subsequently have been confirmed through recent experiments on (Ca,Sr) 3 Ti 2 O 7 single crystals 17 , Ca 3 Ti 2 O 7 and Ca 3 Mn 2 O 7 polycrystals 18 , and Ca 3 (Ti,Mn) 2 O 7 ceramics 19 . In (Ca,Sr) 3 Ti 2 O 7 single crystals, the existence of a switchable P under a small electric field was also demonstrated 17 .…”
mentioning
confidence: 99%
“…Recently it has been shown that in perovskite thin films, improper ferroelectricity may be induced via strain coupling of octahedral rotations between different perovskite heterostructure layers [12]. Benedek and Harris [13,14] developed this idea further proposing a novel mechanism where this improper ferroelectricity may be realized in the bulk structure. In this mechanism, instability of the polar phonon mode is driven by the condensation of two nonpolar lattice modes, neither of which are zone centered.…”
mentioning
confidence: 99%